A survey on patients expectations and level of satisfaction with the health services provided by the pharmacy staff at PPUKM Out Patient Pharmacy - Nor Azman, Nor Farizah; Fakir Mohamed, Nur Nabila (2018)
Patient's satisfaction is becoming a popular health-care quality indicator as it reflects the services provided. The aim of this study is to evaluate the patient's level of satisfaction towards the health care services provided by the Out-Patient Pharmacy department in PPUKM. Our main objective of the study was to assess patient's expectations and satisfaction levels starting from receiving a queue number to receiving the medicines. The secondary objective of the study was to identify the factors that cause dissatisfaction among patients throughout the whole process. A cross sectional study was conducted from November 2017 to December 2017 and a total of 171 respondents were obtained. The questionnaire consists of 24 questions divided to four parts respectively. From the response obtained, we tabulated the data by using the Statistical Package for the Social Sciences (SPSS) Version 16 and Microsoft Office Excel 2010. The results showed that 84.8% (n=145) of the respondents agreed that they received the prescription promptly while 15.2% (n=26) disagreed as they had waited a longer time in order to receive their prescriptions. Furthermore, 82.5% (n= 141) of the respondents say that the pharmacy staffs have the ability to resolve their enquiries at the counter and the rest say otherwise. Most patients agree on receiving their prescriptions efficiently while 18.8% (n=32) of the patients were unsatisfied with the waiting time. Putting all the data together, it appeared that majority respondents agreed that the overall services provided are very good and satisfactory.